When history no longer suffices: Towards uniform rules for armed conflicts - Brits, Pieter (Scientia Militaria - South African Journal of Military Studies, 2017)
The key instruments of International Humanitarian Law (IHL), the 1949 Geneva Conventions and the Additional Protocols of 1977, divides armed conflict into two legal categories: international armed conflicts (IAC) or non-international armed conflicts (NIAC). While international armed conflicts are regulated by the whole range of the Geneva Conventions, there is only one single article, common Article 3 to the Geneva Conventions that provides for non-international armed conflicts. The same applies to the Additional Protocols to the Geneva Conventions of 1977. This is concerning, as the bulk of conflicts since 1945 has been non-international in nature. The end of the 20th century saw an increase in internationalized armed conflicts: conflicts that may have started as internal conflicts but due to third state intervention or the scope and magnitude of the conflict, have become something that transcend categorization as internal armed conflicts. These conflicts can either remain NIAC’s or become IAC’s. Depending on the nature of the parties involved one can even have a situation where the rules to both types of conflicts apply simultaneously with dire legal effects for the parties involved. The events of 11 September 2001 and the so-called “war on terror” brought transnational armed conflicts to the foreground: cross-border conflicts that often fall outside the scope of the classic IAC and also fail to meet the requirement for NIAC’s that requires the conflict to take place “within the territory of one of the High Contracting Parties”. After examining the historical background leading up to the classification of armed conflicts as either IAC or NIAC, the article takes a look at recent developments and ask whether the time has not arrived to do away with the Geneva Convention straightjacket for purposes of determining rules applicable to a particular conflict?